A MODERATION MODEL OF WORK ENVIRONMENT ON THE RELATIONSHIP BETWEEN WORK DISCIPLINE, WORKLOAD, AND EMPLOYEE PERFORMANCE AT PT. PNE - Aprian Herwansyah; Lukmanul Hakim; A.K. Yohanson; Kemas Muhammat Abdul Fatah (ITB AAS Indonesia Surakarta, 2026)
PT Putra Nusa Energy is a company that deals with diesel fuel distribution. There are 40 employees in three divisions. The objective of this study is to evaluate the impact of work discipline, workload, and work environment on employee performance at PT Putra Nusa Energy. The data in this study is quantitative.. Questionnaires filled out on a Likert scale were distributed among all 40 employees, which collected data. The total sampling is conducted using the census method, which involves taking into account the entire population. Using SPSS, the analysis of data was conducted using multiple linear regression and moderated regression analysis (MRA). The study suggests that employee performance can be positively affected by work discipline and work environment. This is a significant finding. However, the negative impact of workload on employee performance is not as significant. Furthermore, the workplace atmosphere greatly amplifies how work discipline can positively influence performance. The relationship between workload and employee performance is significantly tempered. The company must demonstrate a strong commitment to improving work ethics and mitigating the negative effects of workload.' Moreover, the work environment must be maintained as a crucial factor to ensure operational stability. Keywords : Employee Performance, Putra Nusa Energy, Work Discipline, Work Environment, Workload